The art of choosing the right running shoe review article - Romero Cardenas, Carolina (Journal of the Foot & Ankle, 2024)
This review aims to synthesize current knowledge on running biomechanics, structure and materials of running shoes, and critical factors to consider when choosing the right running shoe to enhance performance and reduce injury risk. A search was performed across major electronic databases, including PubMed, EMBASE, Web of Science, and Google Scholar. Selected studies were then analyzed and synthesized to pinpoint the key factors in choosing the right running shoe, including biomechanics, shoe structure, injury prevention, and the benefits and limitations of different running shoe options. The running shoe choice significantly affects the running performance and injury risk. Key features, such as shoe drop, cushioning, stiffness, and weight must be considered based on the runner’s anatomy, gait, and training regimen. Personalized recommendations, informed by a thorough understanding of shoe biomechanics and individual runner needs, are crucial for optimizing the running efficiency and minimizing injuries.